Assessment Of Location And Anatomical Characteristics Of Mental Foramen, Anterior Loop, Mandibular Incisive Canal And Accessory Canal Using Cone Beam Computed Tomography - Tejaswini, Nalagarla Sai; Tejasvi. M.L, Avinash; Tejaswi, Nadella; Ruthvik, Jambula; Amulya, Muthyala; Vasavi, Varkala (Journal of Neonatal Surgery, 2025)
Background: Accurate assessment of the mental foramen (MF), anterior loop (AL), mandibular incisive canal (MIC), and accessory canals (ACs) is essential for successful clinical interventions in the mandibular region. Cone Beam Computed Tomography (CBCT) provides high-resolution three-dimensional imaging that facilitates precise evaluation of these anatomical structures, minimizing the risk of neurovascular complications. Objective: This retrospective study aimed to assess the location, dimensions, and anatomical variations of the MF, AL, MIC, and ACs using CBCT imaging. Methods: A cross-sectional study was conducted on 200 CBCT scans obtained from the Kamineni Institute of Dental Sciences. The scans were evaluated using Carestream Imaging Software 8.0.1.8(9600) in high-resolution mode. Key parameters analyzed included the position and orientation of the MF, the presence and dimensions of the AL, the length and orientation of the MIC, and the distribution of ACs. Measurements were compared between the right and left sides, and statistical analyses were performed using SPSS software, with a significance threshold set at p<0.05. Results: The MF was most commonly located in the buccal position (70% on the right side, 75% on the left side). The mean length of the MIC was 13.5 mm, with no statistically significant differences between genders or sides. The presence of ACs was significantly higher on the right side (15%) compared to the left side (10%) (p=0.046). The AL was present in 20% of cases on both sides, with no statistically significant difference (p=1.000). Other measurements, including distances to the buccal plate, lingual plate, and inferior mandibular border, showed minor variations that were not statistically significant. Conclusion: This study highlights the variability in mandibular anatomy, emphasizing the need for preoperative CBCT imaging to improve diagnostic accuracy and procedural safety. The findings reinforce the importance of individualized treatment planning, particularly in implant placement, endodontics, and surgical interventions. Further research with larger, multi-center studies is recommended to enhance the understanding of mandibular anatomical variations across diverse populations